Global signalling network analysis of luminal T47D breast cancer cells in response to progesterone - Wright, Roni H. G.; Vastolo, Viviana; Oliete, Javier Quilez; Carbonell-Caballero, José; Beato, Miguel (Frontiers in Endocrinology, 2022)
Breast cancer cells enter into the cell cycle following progestin exposure by the activation of signalling cascades involving a plethora of enzymes, transcription factors and co-factors that transmit the external signal from the cell membrane to chromatin, ultimately leading to a change of the gene expression program. Although many of the events within the signalling network have been described in isolation, how they globally team up to generate the final cell response is unclear. In this study we use antibody microarrays and phosphoproteomics to provide a dynamic global signalling map that reveals new key regulated proteins and links between previously known and novel pathways. Detailed analysis of the data revealed intriguing changes in protein complexes involved in nuclear structure, EMT, cell adhesion, as well as transcription factors previously not associated with breast cancer proliferation. As different post-translational modifications can mediate complex crosstalk mechanisms and massive PARylation is also rapidly induced by progestins, we provide details of important chromatin regulatory complexes containing both phosphorylated and PARylated proteins. This study contributes an important resource for the scientific community, as it identifies novel players and connections meaningful for breast cancer cell biology and potentially relevant for cancer management.